Dynamics of arterial hypertension depending on change of weight - I. V. Dolgalyov; V. V. Obraztsov; I. V. Tsimbalyuk; T. Yu. Konko; B. A. Trotsenko; R. S. Karpov (Бюллетень сибирской медицины)
In 17-year cohort p1rospective study, the dynamics of arterial hypertension (AH) and arterial pressure (AP) levels has been examined as functions of the boy mass. The cohort included 630 men and 916 women aged from 20 to 59. The overweight was diagnosed at the Body Mass Index index no lower than 25 kg/m2.In the primary research, the AH prevalence rate was 35,7% among overweighted people and 12,5% (р < 0,001) among people with normal weight. In the 17-year observation, the increase of the body mass up to overweight was accompanied by an increase in the AH rate and AP levels, while the decrease of the body mass down to the normal one was accompanied by a decrease of these indices (except only for men aged from 40 to 59). Among overweighted people revealed at the I and II stages of the study, the systolic ((155,71 ± 28,59) mmHg) and diastolic ((93,68 ± 13,77) mm Hg) AH was higher than that in people, who became overweighted the observation: (137,08 ± 23,02) and (86,73 ± 12,19) mm Hg, respectively (р < 0,001).